Putting in harm to cure: Drug related adverse events do not affect outcome of patients receiving treatment for multidrug-resistant Tuberculosis. Experience from a tertiary hospital in Italy - Gualano, Gina; Mencarini, Paola; Musso, Maria; Mosti, Silvia; Santangelo, Laura; Murachelli, Silvia; Cannas, Angela; Di Caro, Antonino; Navarra, Assunta; Goletti, Delia; Girardi, Enrico; Palmieri, Fabrizio (PloS one, 2019)
Treatment of multi-drug resistant Tuberculosis (MDR-TB) is challenging because it mostly relies on drugs with lower efficacy and greater toxicity than those used for drug-susceptible TB. Aim of the study was to describe the frequency and type of adverse drug reactions in a cohort of MDR-TB patients and their potential impact on treatment outcome. We conducted a retrospective study in a cohort of MDR-TB patients enrolled at a tertiary referral hospital in Italy from January 2008 to December 2016. The records of patients were reviewed for epidemiological, clinical, microbiological and adverse drug reactions data. Seventy-four MDR-TB patients (mean age 32 years, 58.1% males, 2 XDR, 12 pre-XDR TB) were extracted from the Institute data base and included in the retrospective study cohort in the evaluation period (January 2008-December 2016). Median length of treatment duration was 20 months (IQR 14-24). Treatment outcome was successful in 57 patients (77%; 51 cured, 6 treatment completed); one patient died and one failed (2.7% overall); 15 patients were lost to follow-up (20.3%). Sixty-six (89.2%) presented adverse drug reactions during the whole treatment period. Total number of adverse drug reactions registered was 409. Three hundred forty-six (84.6%) were classified as adverse events (AEs) and 63 (15.4%) were serious AEs (SAEs). One third of the total adverse drug reactions (134/409; 32.8%) was of gastrointestinal origin, followed by 47/409 (11.5%) ototoxic drug reactions, thirty-five (8.6%) regarded central nervous system and 33 (8.1%) affected the liver. All 63 SAEs required treatment suspension with 61 SAEs out of 63 (96.8%) occurring during the first six months of treatment. Factors associated with unsuccessful treatment outcome were smoking (p = 0.039), alcohol abuse (p = 0.005) and homeless condition (p = 0.044). Neither the number of antitubercular drugs used in different combinations nor the number of AEs showed significant impact on outcome. Patients who completed the treatment experienced a greater number of AEs and SAEs (p < 0.001) if compared to lost to follow-up patients. Our data demonstrate that, despite the high frequency of adverse drug reactions and long term therapy, the clinical management of MDR-TB patients in a referral center could reach successful treatment according to WHO target, by implementing active and systematic clinical and laboratory assessment to detect, report and manage suspected and confirmed adverse drug reactions.